2015
DOI: 10.1128/aem.00648-15
|View full text |Cite
|
Sign up to set email alerts
|

VirR-Mediated Resistance of Listeria monocytogenes against Food Antimicrobials and Cross-Protection Induced by Exposure to Organic Acid Salts

Abstract: Formulations of ready-to-eat (RTE) foods with antimicrobial compounds constitute an important safety measure against foodborne pathogens such as Listeria monocytogenes. While the efficacy of many commercially available antimicrobial compounds has been demonstrated in a variety of foods, the current understanding of the resistance mechanisms employed by L. monocytogenes to counteract these stresses is limited. In this study, we screened in-frame deletion mutants of two-component system response regulators assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 68 publications
2
47
0
Order By: Relevance
“…Cell envelope stress response systems, including those regulated by VirR (Kang et al . ) and LiaR (Bergholz et al . ), are known to contribute to nisin resistance at low temperatures and in the presence of NaCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell envelope stress response systems, including those regulated by VirR (Kang et al . ) and LiaR (Bergholz et al . ), are known to contribute to nisin resistance at low temperatures and in the presence of NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the significant differences in nisin resistance phenotypes that we present here, it is possible that genetic background plays a larger role in overall nisin resistance phenotypes than simply the presence or absence of SSI-1. Cell envelope stress response systems, including those regulated by VirR (Kang et al 2015) and LiaR , are known to contribute to nisin resistance at low temperatures and in the presence of NaCl. Variation in regulation or expression of these systems could also contribute to the varying nisin resistance phenotypes observed.…”
Section: Discussionmentioning
confidence: 99%
“…H7858 is a lineage I, serotype 4b strain (representing epidemic clone II) isolated from RTE meat and was linked to a multistate listeriosis outbreak from 1998 to 1999 (24,25). We selected H7858 for this study because we had previously quantified the phenotypic and transcriptomic responses of this strain to a number of stresses relevant to food products, including organic acids and bactericidal additives, and know that it can grow to high levels on cold smoked salmon (26)(27)(28). L. monocytogenes H7858 was streaked from frozen BHI stock stored at Ϫ80°C in 15% glycerol onto a BHI agar plate, followed by incubation at 37°C for 24 h. A single colony was subsequently inoculated into 5 ml of BHIB (in 16-mm tubes), followed by incubation at 37°C with shaking (230 rpm) for 18 h (series 25 incubator; New Brunswick Scientific, Edison, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Some examples of antimicrobials which have been proven to be active against L. monocytogenes include lauric arginate, chitosan, pediocin, and nisin (Kaur et al, 2013; Kang et al, 2015). Nisin is one of the most common antimicrobials used in the food industry especially within dairy products and acidic foods (Delves-Broughton et al, 1996).…”
Section: Stresses Encountered In Foodmentioning
confidence: 99%
“…Different systems including two component regulatory systems and the GSR have been implicated in L. monocytogenes resistance to nisin. Kang et al (2015) showed that a mutant deficient in the response regulator VirR had a greater loss of membrane integrity compared to the wild-type strain, while Begley et al (2006) found that a sigB mutant had decreased growth and survival in response to nisin. However, Palmer et al (2009) reported data which conflicted these results.…”
Section: Stresses Encountered In Foodmentioning
confidence: 99%